Production and Partial Characterization of Yellow Pigment Produced by Kocuria flava Isolate and Testing its Antioxidant and Antimicrobial activity.: Life Sciences-Biochemistry for better diagnosis and therapy - Sahar A. Mal; Ghada S. Ibrahim; Maha I. Al Khalaf; Ahmed M. Al-Hejin; Noor Mohammed Bataweel; Mohamed Abu-Zaid (International Journal of Life Science and Pharma Research, 2022)
Recently, Natural pigments produced great interest within the market and made need to find eco-friendlier and less hazardous pigments than synthetic colorants, particularly microbial pigments. This work was undertaken with an aim of isolating pigment producing bacteria from air, then production and extraction pigment from isolated bacteria with antioxidant and antimicrobial properties against pathogenic microorganisms. Bacterium was identified by morphological characteristics and 16S rRNA sequencing as Kocuria flava SIF3, submitted to GenBank (accession number MN162713). Pigment production was carried out using nutrient broth medium (NB). Yellow pigment extracted by using methanol as solvent, showed maximum absorption spectrum (λmax) at 437 nm by UV-VIS spectroscopy and the degree of cell pigmentation was 0.472. Partial characterization of the extracted yellow pigment using UV- VIS spectroscopy and Fourier- Transform Infrared Spectroscopy analysis (FTIR) revealed it to be a carotenoid which has numerous applications. This novel extracted yellow pigment was screened for antimicrobial activity against pathogenic and antioxidant activity. This particular pigment showed inhibitory effect against all tested microbes so it could be chosen as a broad spectrum antimicrobial agent. The maximum zone of inhibition was (20 mm) against Penicillium sp. then Pseudomonas aeruginosa (12mm). The yellow pigment was discovered to have DPPH radical- scavenging activity with an IC50 value of 1.25mg / ml in vitro antioxidant assay. Present findings highlight the significance of yellow pigment extracted from Kocuria flava SIF3. Further purification of pigment will be useful in discovering a promising drug.